Experimental investigation on BOF slag oxidation in air. (14th September 2019) - Jiang, L.; Bao, Y.; Hu, X.; Chen, Y.; Liu, G.; Han, F.; Yang, Q.; Wu, J.
ABSTRACT: Basic oxygen furnace (BOF) slag contains a significant amount of iron-containing species, which is considered to be iron resources and therefore need to be recovered. In this work, the oxidation behaviour of BOF slag under air (at selected oxidation temperatures and holding time) was investigated to explore the potential of transforming non-magnetic wustite in the BOF slag into magnetic spinel, which may subsequently be recovered by magnetic separation. The experimental results show that the iron-containing spices in the BOF slag can be oxidised into magnetic spinel phases in the investigated temperature range of 1000–1150°C and thereafter be recovered by magnetic separation. The formation of these phases is closely related to the oxidation temperatures and holding time: a higher oxidation temperature and longer holding time lead to a larger amount of formed magnetic species; however, the amount of formed magnetic species decreases at elevated temperature (>1050°C) and with extended holding time (>40 min).